Effect of Attachment Style, Self Esteem and Delay of Gratification on Academic Achievement - Kaur, Jasmeet (My University, 2017)
The main aim of the study was to examine the effect of attachment style, self esteem and delay of gratification and academic achievement. One hundred student volunteers (females), of the age range 20-22 years participated in the study. The participants were from Punjab University, Chandigarh. Revised Adult Attachment Scale (RAAS), Rosenberg self esteem scale, Delay of Gratification Inventory were used for measuring Attachment Style, Self Esteem, Delay of Gratification, respectively. It was predicted that self esteem and delay of gratification have appositive effect on academic achievement. In addition to this, attachment style such as close and anxiety has a positive effect on academic achievement, delay of gratification and self esteem. Similarly, the anxiety attachment style is negatively associated with academic achievement. Correlation and regression were used analyze the results. The results indicate that the delay of gratification factor social & money has a positive effect on academic achievement. Out of the attachment style, anxiety attachment style has a negative effect on the overall delay of gratification and also close attachment has a negative effect on delay of gratification for the factor food. The present study found that, the delay of gratification benefits the individuals in achieving higher performance whereas, anxious attachment hampers in attaining delay of gratification. The close attachment style has a negative impact on the delay especially on food
Keywords: attachment style, self esteem, delay of gratification and academic achievement.